2012
DOI: 10.1242/jcs.108597
|View full text |Cite
|
Sign up to set email alerts
|

The Bro1 domain-containing Myopic/HDPTP coordinates with Rab4 to regulate cell adhesion and migration

Abstract: SummaryProtein tyrosine phosphatases (PTPs) are a group of tightly regulated enzymes that coordinate with protein tyrosine kinases to control protein phosphorylation during various cellular processes. Using genetic analysis in Drosophila non-transmembrane PTPs, we identified one role that Myopic (Mop), the Drosophila homolog of the human His domain phosphotyrosine phosphatase (HDPTP), plays in cell adhesion. Depletion of Mop results in aberrant integrin distribution and border cell dissociation during Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…It functions in many cellular processes including phagocytosis, neurogenesis, and cell migration (Stroschein-Stevenson et al 2006; Chen et al 2012). We tested the available Ptpmeg2 P element transposon insert lines and clock cell-specific Ptpmeg2 overexpression flies, but none of these genetic reagents altered activity rhythms (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It functions in many cellular processes including phagocytosis, neurogenesis, and cell migration (Stroschein-Stevenson et al 2006; Chen et al 2012). We tested the available Ptpmeg2 P element transposon insert lines and clock cell-specific Ptpmeg2 overexpression flies, but none of these genetic reagents altered activity rhythms (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EGFR can phosphorylate Clathrin in a Src-mediated mechanism regulating its redistribution [53], can also phosphorylate the endocytic adaptor protein Eps15 [54,55], and can induce E-Cadh macropinocytosis [56]. Interestingly, myopic was shown to regulate EGFR signalling [57] and to interact with Rab4 [58]. Furthermore, Rac1, which can be a target of Receptor Tyrosine Kinases [59], has been shown to regulate Serp and Crb in the trachea [60].…”
Section: Discussionmentioning
confidence: 99%
“…Out of 73 PTPN23 orthologs examined, all but 6 harbor a conserved serine residue (VHCS S GXG) instead of an alanine residue (VHCS A GXG) in the PTP signature motif; it has been suggested that this Ala to Ser mutation in PTPN23 may influence the entry and positioning of the substrate in the catalytic pocket [99]. Besides, the D → K mutation in the WPD loop appears to contribute to Mop 's lack of observed catalytic activity [100]. Despite the abrogation of its catalytic activity, Mop has been reported to act as a tumor suppressor by influencing different signaling pathways, for example through the inhibition of receptor protein kinase signaling during their endocytic internalization [101], and by interacting and regulating the transcription factor Yorkie [102].…”
Section: The Drosophila Tyrosine Phosphatome Is a Streamlined Versionmentioning
confidence: 99%